PRUNING AND NITROGEN FERTILIZATION INTERACTIONS ON GROWTH AND PRODUCTIVITY OF NEW CASTLE APRICOT (Prunus armeniaca L.) TREES - Dr. Dharam Paul Sharma; Dr. Rocky Thokchom; Dr. Kishore Kumar Thakur (Journal of Animal and Plant Sciences, 2025)
This study was motivated by the challenge of declining productivity and vitality in older apricot trees, especially the “New Castle” variety (Prunus armeniaca L.). As these trees age, they often grow more slowly, produce less fruit, and generally become less vigorous, which can threaten both orchard sustainability and economic returns for growers. Traditional approaches, such as fertilization and pruning, are commonly applied to manage tree health, yet the precise combination and intensity of these treatments that best support rejuvenation has not been extensively explored, especially in aging apricot orchards. This research explores the synergistic effects of nitrogen fertilization and pruning interactions. Using a factorial randomized block design, the study examined ten interaction treatments involving three levels of pruning (20%, 40%, and 60%) and three nitrogen fertilization doses (500g, 625g, and 750g N/tree). The findings demonstrate that strategic pruning in combination with appropriate nitrogen doses significantly accelerates tree vigour and fruiting. Notably, the interaction treatment involving light pruning (20%) and the highest nitrogen dose (750g per tree) yielded the most promising results, enhancing tree trunk girth, height, volume, fruit set, and productivity. Substantial pruning (60%) combined with the maximum nitrogen dose (750g per tree), resulted in enhanced canopy spread, increased annual shoot extension, greater pruning wood weight, expanded leaf area, and elevated chlorophyll contents.Crucially, the examined parameters exhibited a reliable and continuous growth trend, progressively increasing from the commencement of the study to its culmination as a result of the various rejuvenation treatments employed. This research sheds light on effective strategies for rejuvenating aging fruit trees and ensuring sustained productivity.
Keywords: aging trees; rejuvenation; synergy; canopy; vigour; fruiting